Property Tax Diagnostic Manual - Kelly, Roy; White, Roland; Anand, Aanchal (World Bank, Washington, DC, 2020)
This Property Tax Diagnostic Manual provides guidance on how to analyze and assess immovable property tax systems, diagnose the strengths and weaknesses of such systems, and develop a property tax intervention strategy where needed. Its higher objective is to support increasingly fair and stable tax systems in low- and middle-income countries, with significant potential for sustainable improvements in achieving key revenue, equity, and efficiency objectives. This Manual focuses specifically on the recurrent, immovable property tax.